kosakata dasar PENINGKATAN KOSAKATA DASAR ANAK USIA DINI MELALUI MEDIA FILM ANIMASI PADA KELOMPOK A DI PAUD AR-RIZQI BOGOR: KOSAKATA DASAR ANAK USIA DINI - Nina Yuminar Priyanti Nina; O’on Fadjria (incrementapedia, 2022)
The Basic Vocabulary of Early Childhood Improvement Using Animated Film Media at group A PAUD Ar-Rizqi Bogor. Panca Sakti University This research aims to improve the basic vocabulary of children at an early age using animated film media in the group A Paud Ar-Rizqi Bogor. This research uses a Class Action Research Model (PTK) with two cycles and four stages in each cycle such as; planning, execution of actions, observations, and reflections. The subjects in the study were 15 children: 9 girls and 6 boys. The condition before the action, the child's basic vocabulary obtained a fairly low result of about 25%. Then after the action in cycle I, the result increased about 53% and it was increased again in cycle II. 80% of children were able to mention basic vocabulary after have seen animated films. The results of this study show that animated film media can be used to improve vocabulary mastery in children. Improving basic vocabulary mastery is part of language development. Through language, children can tell their experiences, and convey through the symbols they use to communicate and think.